Foundation of Acoustics - RAJU, K.M.; KAILASH (SCHOOL SCIENCE, 2006)
Acoustics is the science of sound. In the first century B.C., the Roman architect Vitruvius explained in De architectura, his famous 10-volume treatise on architecture, that sound “moves in an endless number of circular rounds, like the innumerably increasing circular waves which appear when a stone is thrown into smooth water . but while in the case of water the circles move horizontally on a plane surface, the voice not only proceeds horizontally, but also ascends vertically by regular stages”. While Vitruvius did not understand everything sound, he was correct about this particular point.